Study on coupling model of reservoir seepage dynamic and horizontal wellbore flow - Cheng, Zhong; Liu, Jingchao; Zhang, Liang; Zuo, Kai; Liu, Chuangang; Hao, Zhouzheng; Ding, Xiangxiang (Frontiers in Energy Research, 2025)
The dynamic seepage behavior of the reservoir near the wellbore directly affects oil well productivity, fluid properties, and pressure distribution in the wellbore. Accurately describing and understanding this area is crucial for making informed decisions on reservoir management and production optimization, making it one of the current research hotspots. To more accurately characterize the coupled flow behavior between the wellbore and the near-well reservoir, this study proposes a transient coupling prediction model for the wellbore-reservoir system in the completion section of a horizontal well, based on fluid mechanics and reservoir seepage theories. This model addresses the deficiencies of traditional models in describing the interaction of wellbore flow, completion dynamics, and reservoir seepage by explicitly depicting the dynamic interactions between the wellbore and the reservoir. The research results indicate: (1) For the annulus and wellbore, flow rate and pressure stabilize at approximately 100 s, during which complex flow direction information in the annulus is captured, revealing the early transient flow characteristics inside the wellbore. (2) For the reservoir seepage near the wellbore, a larger time interval is selected, and variations in pressure and flow rate are still observed within the 1-day to 10-day range. However, the changes in reservoir pressure and axial flow rate are relatively small, highlighting the spatial and temporal scale differences between the reservoir and wellbore simulations. This coupled model facilitates the evaluation of oil well performance parameters and, by incorporating the behavior of the reservoir near the wellbore, provides theoretical guidance and technical support for production optimization and reservoir management.